A note on voluntary intake and livestock productivity - International Livestock Centre for Africa (International Livestock Centre for Africa, 1982)
Deals with a study in voluntary intake and livestock productivity in the Sahel carried out over a year using a herd of Zebu cattle, with some observations repeated on a flock of Sahelian sheep and goats, both under traditional management. Also presents a comparison to herds elsewhere.